HLA B37 determines an influenza A virus nucleoprotein epitope recognized by cytotoxic T lymphocytes (The Rockefeller University Press, 1986)
Human influenza A virus-specific, cytotoxic T cells have been shown previously to recognize the virus nucleoprotein on infected cells. CTL preparations from four HLA B37-positive donors were shown to recognize a synthetic peptide that corresponded to amino acids 335-349 of the nucleoprotein sequence. Influenza-specific CTL from 10 donors of other HLA types failed to recognize this epitope. CD8+ CTL lines were derived from lymphocytes of two HLA B37-positive donors and used to show that the peptide was represented on virus-infected cells and to determine the probable boundaries of the epitope.